GZ17-6.02 and Pemetrexed Interact to Kill Osimertinib-Resistant NSCLC Cells That Express Mutant ERBB1 Proteins - Booth, Laurence; West, Cameron; Moore, Robert P.; Von Hoff, Daniel; Dent, Paul (Frontiers in Oncology, 2021)
We determined the molecular mechanisms by which the novel therapeutic GZ17-6.02 killed NSCLC cells. Erlotinib, afatinib and osimertinib interacted with GZ17-6.02 to kill NSCLC cells expressing mutant EGFR proteins. GZ17-6.02 did not interact with any EGFR inhibitor to kill osimertinib resistant cells. GZ17-6.02 interacted with the thymidylate synthase inhibitor pemetrexed to kill NSCLC cells expressing mutant ERBB1 proteins or mutant RAS proteins or cells that were resistant to EGFR inhibitors. The drugs interacted to activate ATM, the AMPK and ULK1 and inactivate mTORC1, mTORC2, ERK1/2, AKT, eIF2 alpha and c-SRC. Knock down of ATM or AMPK alpha1 prevented ULK1 activation. The drugs interacted to cause autophagosome formation followed by flux, which was significantly reduced by knock down of ATM, AMPK alpha1, eIF2 alpha, or by expression of an activated mTOR protein. Knock down of Beclin1, ATG5 or [BAX + BAK] partially though significantly reduced drug combination lethality as did expression of activated mTOR / AKT / MEK1 or over-expression of BCL-XL. Expression of dominant negative caspase 9 weakly reduced killing. The drug combination reduced the expression of HDAC2 and HDAC3 which correlated with lower PD-L1, IDO1 and ODC levels and increased MHCA expression. Collectively, our data support consideration of combining GZ17-6.02 and pemetrexed in osimertinib resistant NSCLC.